Drosophila seminal sex peptide associates with rival as well as own sperm, providing SP function in polyandrous females - Misra, Snigdha; Wolfner, Mariana F (eLife, 2020)
When females mate with more than one male, the males’ paternity share is affected by biases in sperm use. These competitive interactions occur while female and male molecules and cells work interdependently to optimize fertility, including modifying the female’s physiology through interactions with male seminal fluid proteins (SFPs). Some modifications persist, indirectly benefiting later males. Indeed, rival males tailor their ejaculates accordingly. Here, we show that SFPs from one male can directly benefit a rival’s sperm. We report that Sex Peptide (SP) that a female Drosophila receives from a male can bind sperm that she had stored from a previous male, and rescue the sperm utilization and fertility defects of an SP-deficient first-male. Other seminal proteins received in the first mating ‘primed’ the sperm (or the female) for this binding. Thus, SP from one male can directly benefit another, making SP a key molecule in inter-ejaculate interaction.
Keywords: seminal fluid protein; fertility; copulation-complementation; sperm competition; sperm-binding; post-mating response